1991
DOI: 10.1085/jgp.97.6.1279
|View full text |Cite
|
Sign up to set email alerts
|

The nature and origin of spontaneous noise in G protein-gated ion channels.

Abstract: A B S TRACT Arrival of agonist is generally thought to initiate the signal transduction process in G protein-receptor coupled systems. However, the muscarinic atrial K + (K+[ACh]) channel opens spontaneously in the absence of applied agonist, giving a noisy appearance to the current records. We investigated the nature and origin of the noise by measuring single channel currents in cell-attached or excised, insideout membrane patches. Guanosine triphosphate (GTP) produced identical single channel currents in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…As will be outlined in the discussion below, our findings are best interpreted by the two following assumptions: (1) an agonist-independent/mAChR-dependent mechanism mediates a spontaneous activation of Gi, as has been recently suggested for GK by Ito, Sugimoto, Kobayashi, Takahashi &Kurachi (1991) andOKabe et al (1991). As a result, cardiac adenylyl cyclase is under a tonic Gi-mediated inhibition which holds back its basal and/or hormonally stimulated activity; (2) in addition to displacing muscarinic agonists from their binding site on the mAChR, atropine and 'M2-selective' antagonists exhibit intrinsic negative activity on the cardiac mAChR which leads to a reduced interaction between the receptor and the corresponding G proteins, Gi and GK.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…As will be outlined in the discussion below, our findings are best interpreted by the two following assumptions: (1) an agonist-independent/mAChR-dependent mechanism mediates a spontaneous activation of Gi, as has been recently suggested for GK by Ito, Sugimoto, Kobayashi, Takahashi &Kurachi (1991) andOKabe et al (1991). As a result, cardiac adenylyl cyclase is under a tonic Gi-mediated inhibition which holds back its basal and/or hormonally stimulated activity; (2) in addition to displacing muscarinic agonists from their binding site on the mAChR, atropine and 'M2-selective' antagonists exhibit intrinsic negative activity on the cardiac mAChR which leads to a reduced interaction between the receptor and the corresponding G proteins, Gi and GK.…”
Section: Discussionmentioning
confidence: 72%
“…Also it remains unclear to what extent G proteins sustain a spontaneous agonist-independent activation under in vivo conditions. If not negligible, this basal G protein activation is likely to affect adenylyl cyclase and IK(ACh) Interestingly, it has been shown that single mAChR-activated K+ channels can open spontaneously even in the absence of mAChR stimulation (Soejima & Noma, 1984;Kaibara, Nakajima, Irisawa & Giles, 1991;Okabe et al 1991;Ito et al 1991) and that this spontaneous activity can be totally suppressed by pertussis toxin pretreatment (but see Kaibara et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Potassium channels regulated by GTP-binding proteins, which exhibit inward rectification, have been identified in a number of cells including osteoclasts (Okabe et al 1991;Arkett et al 1994). Furthermore, estrogen has been shown to block K + conductance through a second-messenger system involving cAMP in hypothalamic neurons (Minami et al 1990).…”
mentioning
confidence: 99%
“…3. Spontaneous, i. e. agonist-independent opening activity, which is an intrinsic property of this channel species, caused by agonist-independent G-protein and channel interaction [11,21], has been recorded starting about 5 s after formation of the seal. The figure depicts a sequence of traces, each corresponding to 6 s, interrupted by periods of 12 s, i. e. the entire recording covers a period of time of about 8 min.…”
Section: Resultsmentioning
confidence: 99%